Market Concentration and International Outsourcing - Hartmut Egger; Peter Egger (Austrian Institute of Economic Research (WIFO), 2001)
This paper shows that market concentration is positively related to outsourcing activities in a framework of Cournot competition with strategic outsourcing in a first stage. The theoretical priors are confirmed by rank correlation coefficients between the intermediate goods import intensity and market concentration in the EU12 countries.
Keywords: F12; F15; F40; L13; 330; International outsourcing; Oligopolistic competition; Marktmacht; Outsourcing; Oligopol; Marktstruktur; Theorie